2005
DOI: 10.1007/s00701-005-0624-1
|View full text |Cite
|
Sign up to set email alerts
|

Ability of navigated 3D ultrasound to delineate gliomas and metastases – comparison of image interpretations with histopathology

Abstract: Reformatted images from 3D US volumes give a good delineation of metastases and the solid part of gliomas before starting the resection. Navigated 3D US is at least as reliable as navigated 3D MR to delineate gliomas and metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 21 publications
1
76
0
1
Order By: Relevance
“…2 Intraoperative ultrasonography provides reliable real-time updates of the operative field ("live anatomy"). 4,10,14,25,34,35,37 The limitation of ultrasound in delineating residual tumor is mainly related to 2 issues: image quality and anatomical orientation. Recent advances in ultrasound technology have significantly improved resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Intraoperative ultrasonography provides reliable real-time updates of the operative field ("live anatomy"). 4,10,14,25,34,35,37 The limitation of ultrasound in delineating residual tumor is mainly related to 2 issues: image quality and anatomical orientation. Recent advances in ultrasound technology have significantly improved resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Good-quality ultrasound images have been shown to be comparable to MR images in delineating brain tumors. 6,34 Therefore, in our opinion, little advantage is gained by using the preoperatively acquired MR images (especially once brain shift has occurred). Also, in many cases, logistical challenges make it difficult to organize preoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative neurosurgical techniques to maximize resection (e.g. image-guided surgery, [58] ultrasonography, [59] and introduction of fluorescence-guided surgery [60] ) and to minimize neurological deficits by electrophysiological techniques [58] improved the likelihood of complete and safe removal of metastases. A combination of surgery plus radiation in patients with up to three CNS metastases can improve survival and preserve functional independence, as outlined in two prospective studies [61,62] and three retrospective studies.…”
Section: Local Therapeutic Strategies: Neurosurgical Intervention Andmentioning
confidence: 99%
“…These images can then be displayed with the corresponding MR images to better orient the user, an attractive solution for most neurosurgeons. To assess the usefulness of 3D US in detected tumor, Unsgaard et al (2005) compared 3D ultrasound with preoperative MR images in 28 tumor cases and found that ultrasound was at least as good as MRI in identifying tumor borders. Other studies have also validated the a c c u r a c y o f U S i n b r a i n t u m o r s u r g e r y .…”
Section: Ultrasound Co-registered With Mrimentioning
confidence: 99%
“…Similarly, van Velthoven et al [23] found that ultrasound is as reliable as MRI to delineate gliomas, metastases and meningiomas. In fact, it may even be superior to MRI in defining low-grade tumor boundaries (Unsgaard et al, 2005). Three dimensional US may be useful in identifying tumor, but does its lead to an increased extent of resection?…”
Section: Ultrasound Co-registered With Mrimentioning
confidence: 99%